The Effects of Psychodrama and Cognitive Behavioral Therapy-Based Group Work on Test Anxiety - Necla Taspinar Goveci (Bilişsel Davranışçı Psikoterapi Araştırmalar Dergisi, 2017)
The objective of this research is analyzing comparatively the positive effects of the group counseling practices performed by using the psychodrama techniques in company with the cognitive -behavioral techniques on reducing the exam anxiety of the students. The research having two experimental groups and a control group is a quasi-experimental study based on pretest-posttest design. The research is performed with the students of a private school in Istanbul attending the 10th and the 11th classes. At the end of the practice and evaluation, 32 students having the maximum exam and trait-continuity anxiety levels have been chosen. Randomly 10 students for cognitive behavioral therapy group; 11 students for psychodrama group; and 11 students for control group have been assigned. Exam anxiety thats the dependent variable of the research has been measured by using Exam Anxiety Inventory. Trait and continuity anxiety levels have been measured by Trait-Continuity Anxiety Scale as the other dependent variables of the research. Scales have been given to the experimental and control groups as pretests. By the researcher 10 sessions of psychological consultation by using the psychodrama techniques for the first experimental group; and 8 sessions of psychological consultation by using cognitive behavioral therapy techniques for the second experimental group have been performed. For the control group, no work has been done. After the practices, the scales have been given again as the last test. The data obtained as a result of the experimental work has been analyzed by applying the Kruskal Wallis-H test, Mann Whitney-U test and Wilcoxon test. According to the obtained data it is observed that; compared to the control group, the psychological consultation practices performed by using the psychodrama techniques have been effective on exam anxiety total point, perception, delusion and trait anxiety points. No effect has been detected on continuity anxiety points. On the other hand, it is observed that compared to the control group, the psychological consultation practices performed by using the cognitive behavioral techniques have been effective on exam anxiety total point, perception and delusion. But no affect has been detected on trait and continuity anxiety points. In the analyses relating to comparison; in terms of total exam anxiety, perception, delusion sublevel and trait anxiety points of the students, psychodrama techniques applied in the first group have been more affective with reference to the cognitive behavioral techniques applied in the second group. No meaningful difference has been detected when two experimental groups have been compared according to continuity anxiety points. [JCBPR 2017; 6(1.000): 22-30]